Targeting C-fibers for Peripheral Acting Anti-tussive Drugs - Patil, Mayur J. (Pulm Pharmacol Ther, 2019)
Activation of vagal C-fibers is likely involved in some types of pathological coughing, especially coughing that is associated with airway inflammation. This is because stimulation of vagal C-fibers leads to strong urge to cough sensations, and because C-fiber terminals can be strongly activated by mediators associated with airway inflammation. The most direct manner in which a given mediator can activate a C-fiber terminal is through interacting with its receptor expressed in the terminal membrane. The agonist-receptor interaction then must lead to the opening (or potentially closing) of ion channels that lead to a membrane depolarization. This depolarization is referred to as a generator potential. If, and only if, the generator potential reaches the voltage necessary to activate voltage-gated sodium channels, action potentials are initiated and conducted to the central terminals within the CNS. Therefore, there are three target areas to block the inflammatory mediator induced activation of C-fiber terminals. First, at the level of the mediator-receptor interaction, secondly at the level of the generator potential, and third at the level of the voltage-gated sodium channels. Here we provide a brief overview of each of these therapeutic strategies.